THE IMPACT OF ON-TIME PERFORMANCE TOWARDS QUALITY OF URBAN BUS SERVICES: A CASE STUDY IN STATE CAPITALS OF PENINSULAR MALAYSIA - Abu Bakar M.F.; Norhisham S.; Saad N.M.; Katman H.Y.; Ibrahim M.R.; Yukawa S.; Masjuki S.A.; Abu Bakar N.I. (Malaysian Institute Of Planners, 2024)
Urbanisation have given significant impact on escalating the traffic volume as the tremendous traffic congestion daily, especially during peak hours in weekdays. The objective of this paper is to assesses the impact of on-time performance towards quality of urban bus services in Malaysia. Therefore, this study was conducted at 11 state capitals in Peninsular Malaysia. The main local bus terminals had been designated in this study. The Transit Capacity and Quality of Service Manual (TCQSM, 2013) was chosen as the guideline used in this study. The results showed that Johor Bahru recorded a total 648 departure daily which considered the highest departure. There were 4 state capitals that recorded more than 80% of overall on-time departure for each route, such as Kuala Terengganu (94.39%), Shah Alam (82.45%,), Ipoh (80.74%) and Kangar (80.06%). The overall quality of services for on-time performance in state capitals of Peninsular Malaysia was classified as QOS D. Based on the study results, several rectifications on bus services in state capitals of Peninsular Malaysia is highly required. 2023 by MIP.